A crowding-dependent population model for woody weeds – Where size does matter. (February 2016) - Zull, A.F.; Lawes, R.A.; Cacho, O.J.
Abstract: Integrated weed management for woody weeds is difficult to implement, partly due to the unknown effects of plant size on intraspecific plant competition. Moreover, weed literature often uses density (quantity) as a measure of control efficacy; this is insufficient for woody weeds due to varying plant sizes within populations. Using Ziziphus mauritiana as a case study, we describe a method of simultaneously measuring plant sizes and density: crowdedness. A new deterministic crowding-dependent matrix population model was developed by grouping the population into ten life stages. Elasticity analyses and simulations showed that removing the largest plant had the greatest control efficacy on new and old infestations in riparian and upland zones; despite subsequent mass recruitments. The model also accommodated for shocks without overcompensating. The alternative measure of plant abundance developed in this paper, provides a useful tool to assist in woody-weed control decisions and provide a better measure of weed-control efficacy. Highlights: Woody weeds cause significant economic and environmental damage. Controlling them requires consideration of changes in both plant density and size. We provide a method of concurrently measuring plant sizes and density: crowdedness. The model is solid and accommodates for shocks without overcompensating. Removing large plants had the greatest control efficacy; despite mass recruitments.